2018
DOI: 10.1002/jemt.23043
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between histopathologic and dermoscopic findings in Korean actinic keratosis

Abstract: Skin biopsy for AK diagnosis is usually performed on only a limited part of the whole lesion. Therefore, a clinical diagnosis is important. According to a study, there is no significant correlation between histopathological and clinical classification system. We examined the correlation between microscopic information and dermoscopic findings to deduce if dermoscopic information reflects histopathologic grade severity. Forty seven patients with histologically confirmed AK were enrolled and positive ratio of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
1
7
2
Order By: Relevance
“…17 A more recent study indicated that there were no significant correlations between dermoscopic findings and histological AK classification. 18 In contrast to these studies, our analysis demonstrated the significant correlation between dermoscopic and AK gradings. Furthermore, some dermoscopic characteristics were associated with histopathological features.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…17 A more recent study indicated that there were no significant correlations between dermoscopic findings and histological AK classification. 18 In contrast to these studies, our analysis demonstrated the significant correlation between dermoscopic and AK gradings. Furthermore, some dermoscopic characteristics were associated with histopathological features.…”
Section: Discussioncontrasting
confidence: 95%
“…Schmitz et al demonstrated the lack of correlation between Olsen clinical classification and Roewert‐Huber histological classification in 892 actinic keratoses, suggesting it was not possible to draw conclusions about the histopathology of AK lesions from their clinical appearance 17 . A more recent study indicated that there were no significant correlations between dermoscopic findings and histological AK classification 18 . In contrast to these studies, our analysis demonstrated the significant correlation between dermoscopic and AK gradings.…”
Section: Discussioncontrasting
confidence: 93%
“…In this form, the lesion has an atrophic epidermis on histopathology [5]. According to one study, atrophic type AK more commonly presents with red pseudonetwork [37].…”
Section: Variants Of Akmentioning
confidence: 99%
“…Skilled observers can predict the histologic grade of AK with dermatoscopy, although in consensus with clinical features some studies do not find such correlations [37,38]. The following dermatoscopic-histopathologic correlations have been previously proposed:…”
Section: Dermatoscopic-histopathologic Correlations Of Akmentioning
confidence: 99%
“…Actinic keratosis (AK) is a cutaneous neoplasm that arises on chronically sun-exposed skin. For years, AK was considered to be a separate entity from squamous cell carcinoma (SCC) [1], a premalignant lesion; however, in recent years this concept has been challenged, and now most authors consider AK the continuum of SCC [2][3][4]. The rate of progression to SCC differs greatly among the studies, ranging from 0.025%-20% per year [5,6]; however, it has been doc-umented that 60%-80% of SCCs arise from AK.…”
Section: Introductionmentioning
confidence: 99%